2017
DOI: 10.11648/j.cajph.20170306.12
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Malaria Prevention in Cameroon Through Community Participation: An in-Depth Review

Abstract: Abstract:Despite 66 percent reduction in mortality between 2000 and 2015, malaria remains a major global public health problem, affecting mostly Sub-Saharan Africa. Cameroon remains endemic to malaria, with about 41 percent suffering at least one episode of malaria, annual overall mortality of 30 to 35 percent and 67 percent childhood mortality. Cameroon government's subsidy on artemisinin combination therapy (ACT) for uncomplicated malaria, intermittent preventive treatment for pregnant women (IPTp), free dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…With education, the results revealed that all individuals with at least primary level of education correctly attributed the cause of malaria to a mosquito. This was in line with a study conducted in Douala, Cameroon [ 28 ], which found that the level of education was associated with the correct knowledge on the causative agent of malaria. It is, therefore, not surprising of the findings as governmental interventions to increase access to education in Ghana could have an additional effect of improving the overall health outcomes of the under-five population regarding malaria prevention in future.…”
Section: Discussionsupporting
confidence: 90%
“…With education, the results revealed that all individuals with at least primary level of education correctly attributed the cause of malaria to a mosquito. This was in line with a study conducted in Douala, Cameroon [ 28 ], which found that the level of education was associated with the correct knowledge on the causative agent of malaria. It is, therefore, not surprising of the findings as governmental interventions to increase access to education in Ghana could have an additional effect of improving the overall health outcomes of the under-five population regarding malaria prevention in future.…”
Section: Discussionsupporting
confidence: 90%
“…The global burden and economic impact of the disease are disproportionately high in sub-Saharan Africa, primarily among children under the age of 5 years (WHO, 2021), with an estimated direct cost of at least US$12 billion each year, with costs affecting both individuals and governments (CDC, 2021). In Cameroon, deaths caused by malaria constitute 30%-35% of the overall fatality and 67% of the yearly pediatric mortality figures (Mbako, 2017).…”
Section: Introductionmentioning
confidence: 99%